2017
DOI: 10.1002/jcsm.12248
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin K activity controls cardiotoxin‐induced skeletal muscle repair in mice

Abstract: BackgroundCathepsin K (CatK) is a widely expressed cysteine protease that has gained attention because of its enzymatic and non‐enzymatic functions in signalling. Here, we examined whether CatK‐deficiency (CatK−/−) would mitigate injury‐related skeletal muscle remodelling and fibrosis in mice, with a special focus on inflammation and muscle cell apoptosis.MethodsCardiotoxin (CTX, 20 μM/200 μL) was injected into the left gastrocnemius muscle of male wild‐type (CatK+/+) and CatK−/− mice, and the mice were proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 54 publications
(144 reference statements)
1
28
0
Order By: Relevance
“…Recent in silico and in vitro studies reported that cathepsins K, L, and S could cleave fibrinogen and fibrin, resulting in fragments that differ from the ones produced by plasmin, which opened the door to further investigate their roles in vascular homeostasis, especially in coagulation-associated diseases [174,175]. Moreover, cathepsin K was recently demonstrated to have an essential role in skeletal muscle remodeling, dysfunction, and fibrosis following injury [176]. The roles of cysteine cathepsins in tissue remodeling are diverse and can be both detrimental and beneficial; therefore, cysteine cathepsins are emerging as possible targets in therapeutic strategies.…”
Section: Ecm Proteolysis and The Cathepsinsmentioning
confidence: 99%
“…Recent in silico and in vitro studies reported that cathepsins K, L, and S could cleave fibrinogen and fibrin, resulting in fragments that differ from the ones produced by plasmin, which opened the door to further investigate their roles in vascular homeostasis, especially in coagulation-associated diseases [174,175]. Moreover, cathepsin K was recently demonstrated to have an essential role in skeletal muscle remodeling, dysfunction, and fibrosis following injury [176]. The roles of cysteine cathepsins in tissue remodeling are diverse and can be both detrimental and beneficial; therefore, cysteine cathepsins are emerging as possible targets in therapeutic strategies.…”
Section: Ecm Proteolysis and The Cathepsinsmentioning
confidence: 99%
“…In this model, the ischemic heart was only subjected to 60-120 min reperfusion and then harvested (44). Therefore, cardiac fibrosis or remodeling, including changes in histology and protein biomarkers (matrix metallopeptidase-2/-9 and cathepsins S/K) (45-48), could not be observed in this model within this short period of time. Finally, considerable evidence indicates that reactive oxygen species (ROS) have a predominant role in myocardial damage induced by reperfusion (49,50).…”
Section: Discussionmentioning
confidence: 86%
“…Phosphorylation of TFEB, a well-known master controller of lysosomal biogenesis ( Vega-Rubin-De-Celis et al, 2017 ), was also elevated and translocated from the cytosol to the nucleus during muscle differentiation ( Figure 4A ). In addition, as number of increased lysosome, we investigated activity of Cathepsin B, D, and K, well-known represented lysosomal hydrolase ( Kirschke et al, 1983 ; Colella et al, 1986 ; Bechet et al, 1991 ; Ebisui et al, 1994 ; Ogasawara et al, 2018 ). Cathepsin B, D, and K activities were elevated during muscle differentiation ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%